The authentic teaching of professional competences. A Project of reciprocal learning Secondary School-University - Monereo, Carles; Sànchez-Busqués, Sonia; Suñé, Núria (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The present investigation is part of a project of teaching innovation – ARCPRO – consisting in the reciprocal promotion of professional competences between psychology students at the Autonomous University of Barcelona and teachers in two high schools. The study starts from a design in which three experimental conditions are compared: real advising with notes (students play the role of advisor and they can use their notes during the individual evaluation test), real advising without notes and virtual advising (on the basis of the simulation of a real situation through a LMS Moodle). The results indicate that teaching based on authenticity criteria promotes the acquisition of professional competencies for both, university students and high school teachers, which was very motivating for all participants. The advantages notes and their consequences are also discussed.